Pendampingan Pencatatan Keuangan Sederhana Untuk Wirausaha Biji Delima Di Surabaya - Permatasari, Anita; Yuniarsih, Nia (Universitas Negeri Gorontalo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting the national economy, including in the traditional culinary sector such as biji delima (sago pearl dessert) businesses in Surabaya. Despite having promising market potential, most biji delima entrepreneurs lack an adequate financial recording system. This results in their inability to monitor cash flow, calculate profits and losses, and make effective business decisions. This community service activity aims to improve the financial literacy of biji delima entrepreneurs through training and assistance in simple financial recordkeeping. The method includes initial observation, material preparation, participatory training, individual mentoring, as well as pre-test and post-test evaluations. The results show significant improvements in financial recording practices: 80% of participants began recording daily cash flow, 70% separated personal and business finances, and 60% were able to prepare a simple profit and loss statement. This activity demonstrates that practical-based assistance can enhance the understanding and discipline of MSME actors in managing their business finances. The program is expected to be implemented sustainably and extended to other micro-enterprise sectors.